Division of Inherited Wealth in Customary Marriages in Gayo Lues Regency: An Analysis from the Perspective of the Compilation of Islamic Law - Ramadhan Ariga; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the division of inherited wealth in customary marriages within the Gayo Lues Regency, focusing on the interplay between local cultural practices and the principles outlined in the Compilation of Islamic Law. Inheritance is a critical aspect of social and economic stability, and understanding how it is managed in this unique context is essential for promoting equity and justice. The research delves into the specific customs that govern inheritance distribution among the Gayo Lues community, examining how these practices align or conflict with Islamic legal frameworks. Through qualitative analysis, including interviews and case studies, the study reveals the complexities families face in navigating customary and religious obligations. Key findings indicate that while customary practices are deeply rooted in the community's identity, there is a growing need for harmonization with Islamic law to ensure fair and just distribution of wealth. The study also highlights the role of community leaders and religious authorities in mediating disputes and educating the public about their rights under both customary and Islamic law. Ultimately, this research aims to provide valuable insights for policymakers, legal practitioners, and community leaders, emphasizing the importance of integrating cultural sensitivity with legal frameworks to enhance the understanding and implementation of inheritance rights. The study seeks to contribute to social justice and economic empowerment in the Gayo Lues Regency by fostering dialogue and collaboration between customary and Islamic legal systems.